Pengaruh Penerapan Metode Eksperimen Pada Materi Penjernihan Air Dalam Pembelajaran IPA - ila isrwaty (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2020)
The purpose of this study was to determine whether there was an influence on the application of the experimental method to the learning outcomes of water purification material in science learning in class V. The application of this experimental method was carried out through 5 stages which included: 1) Initial Experimentation, (2) Observation, (3 ) Initial Hypothesis, (4) Verification, (5) Evaluation. The procedure of this study was carried out in three stages, namely; (1) Giving Pretest, (2) Giving Treatment, (3) Giving Posttest. It was obtained from this research through the results of pretest and posttest data analysis, that the application of the experimental method had an effect on learning outcomes in water purification materials in science learning in class V. This was because in the experimental method students were actively involved in proving the theory being studied. Knowledge gained by students will be firmly embedded in their memories because they gain their knowledge through experience.